2022
DOI: 10.47191/ijsshr/v5-i12-59
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Capital Structure of Small and Medium Enterprises in Indonesia

Abstract: This research aims to analyze the determinants of capital structure. The independent variables in this study are corporate taxes, company size, tangible assets, corporate risk, profitability, non-debt tax protection, and liquidity. While the dependent variable is short-term debt, long-term debt, and total debt. The sample of this study uses 61 Small and Medium Enterprises companies listed on the Pefindo Index for the period of 2019-2021. The sampling technique uses purposive sampling and the analysis method us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…These results are consistent with the trade-off theory which explains that large firms have more diversity and less chance of bankruptcy than smaller ones. On the other hand, in the study of SMEs in Indonesia within 2019-2022, Hailla and Leon (2022) have shown the existence of a negative and insignificant effect in relation to firm size and long term debt. Long and Milan (2023) also discovered a significant negative impact of firm size on capital structure (debt ratio).…”
Section: Empirical Review 231 Firm Size and Capital Structure Decisionmentioning
confidence: 98%
See 3 more Smart Citations
“…These results are consistent with the trade-off theory which explains that large firms have more diversity and less chance of bankruptcy than smaller ones. On the other hand, in the study of SMEs in Indonesia within 2019-2022, Hailla and Leon (2022) have shown the existence of a negative and insignificant effect in relation to firm size and long term debt. Long and Milan (2023) also discovered a significant negative impact of firm size on capital structure (debt ratio).…”
Section: Empirical Review 231 Firm Size and Capital Structure Decisionmentioning
confidence: 98%
“…These differences in capital structure are also influenced by additional factors, and this is of particular relevance to MSMEs which have led to studies from a number of researchers on factors that influence or determine capital structure across countries. Although, diverse studies exist in relation to what affect capital structure choices or access to finance by MSMEs in developed and developing countries (as ELbekpashy & ELgiziry, 2018 in Egypt; Forte et al, 2013 in Brazil;Hailla & Leon, 2022;Long & Milan, 2023 in Visegrad group; Lussuamo & Serrasqueiro, 2019 in Angola;Muiru & Kamau, 2014 in Kenya;Oppong-Boakye et al, 2013 in Ghana;Rossi, 2014 in Italy;Rao et al, 2019in India, Arzubiaga et al, 2023 in Spain; Uyar & Guzelyurt, 2015 in Turkey); this area of research is still underexplored in Nigeria as a large number of studies lay emphasis on big and quoted firms and listed firms and the results obtained from these studies cannot be generalized for MSMEs due to their peculiarities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations